2003
DOI: 10.1016/s0735-1097(03)00554-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effects of age and gender on the clinical course of long QT syndrome by genotype

Abstract: During childhood, the risk of cardiac events was significantly higher in LQT1 males than in LQT1 females (hazard ratio [HR] = 1.72), whereas there was no significant gender-related difference in the risk of cardiac events among LQT2 and LQT3 carriers. During adulthood, LQT2 females (HR = 3.71) and LQT1 females (HR = 3.35) had a significantly higher risk of cardiac events than respective males. The lethality of cardiac events was highest in LQT3 males and females (19% and 18%), and higher in LQT1 and LQT2 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
169
3
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 253 publications
(187 citation statements)
references
References 16 publications
6
169
3
6
Order By: Relevance
“…This result corresponds with experimental findings in healthy animals 16,17) and supports the clinical observation that female gender is an independent risk factor for TdP. 2,9,10) Several cellular mechanisms have been implicated in EAD formation in ventricular muscle, including I Ca,L reactivation, Na-Ca exchange current enhancement, and I na reactivation. 11,26) In human VMs, we previously demonstrated that VMs with longer APs are predisposed to develop EADs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result corresponds with experimental findings in healthy animals 16,17) and supports the clinical observation that female gender is an independent risk factor for TdP. 2,9,10) Several cellular mechanisms have been implicated in EAD formation in ventricular muscle, including I Ca,L reactivation, Na-Ca exchange current enhancement, and I na reactivation. 11,26) In human VMs, we previously demonstrated that VMs with longer APs are predisposed to develop EADs.…”
Section: Discussionsupporting
confidence: 89%
“…[6][7][8] Mirroring these gender disparities in ECG variables, there are striking gender disparities in the incidence of cardiac arrhythmias. 1,2) Among the most notable examples are inherited 9) and acquired (eg, secondary to drug use) 10) long QT syndrome (LQTS), where women are far more likely than men to sustain torsade de pointes (TdP) ventricular tachycardia.…”
mentioning
confidence: 99%
“…15 Demographic characteristics among patient groups, such as sex, age at first event, and mean age first seen in clinic for the event, tend to vary by genotype (Table 2). 14,15,26 The frequency of cardiac events (syncope, aborted cardiac arrest and sudden death) tends to be higher in individuals with LQT2 mutations than in those with LQT1 or LQT3 mutations. However, a higher percentage of lethal events by age 40 is associated with the LQT3 genotype.…”
Section: Disease Trends In Disease Severitymentioning
confidence: 99%
“…However, a higher percentage of lethal events by age 40 is associated with the LQT3 genotype. 26 Inheritance patterns and complexity of disease presentation Inherited LQTS manifests in two different forms. The more common familial form, referred to as the Romano-Ward syndrome (RWS), displays the cardiac electrophysiologic abnormalities of LQTS and normal hearing.…”
Section: Disease Trends In Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation